2022
DOI: 10.1186/s42836-022-00131-w
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of policy changes and the covid-19 pandemic on the same day discharge and complications following total hip arthroplasty: a nationwide analysis

Abstract: Introduction As a result of the SARS-CoV-2 (COVID-19) pandemic in 2020, elective surgeries, including total joint arthroplasty (TJA), were suspended nationwide. Concurrent removal of total hip arthroplasty (THA) from the Medicare inpatient-only list posed challenges to the delivery of quality patient care with low payor cost. Therefore, the objective of this study was to compare temporal trends in patient demographics, case volumes, length of stay, and complications following elective THA in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
(44 reference statements)
2
8
0
Order By: Relevance
“…Contrary to our hypothesis, we found no significant difference in the patient sex, race, BMI, smoking status, or age between the two groups. This is in concurrence with Gordon and colleagues, who analyzed the demographics of THA patients in the post-COVID period on the national scale [ 9 ]. Of note, there are few studies analyzing these particular demographic characteristics in TJA patients in the post-COVID period.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Contrary to our hypothesis, we found no significant difference in the patient sex, race, BMI, smoking status, or age between the two groups. This is in concurrence with Gordon and colleagues, who analyzed the demographics of THA patients in the post-COVID period on the national scale [ 9 ]. Of note, there are few studies analyzing these particular demographic characteristics in TJA patients in the post-COVID period.…”
Section: Discussionsupporting
confidence: 82%
“…Our analysis of LOS revealed that 2020 TJA patients stayed in the hospital a significantly shorter amount of time when compared to their 2019 counterparts. A decrease in LOS was also observed nationally in the post-COVID period [ 9 ]. This reflects a significant shift to outpatient TJA operations as opposed to the more standard inpatient protocol [ 11 ].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This likely occurred because orthopedic surgeons were concerned about their patients becoming infected in hospital systems and preferred that patients recover at home when possible. These same trends were found for total shoulder arthroplasty and total joint arthroplasty of the lower extremity [ 22 – 24 ]. Despite this increase, we did not see any difference in overall complication rates, or any subcategory of complications.…”
Section: Discussionsupporting
confidence: 73%
“…Similar results were reported by several authors [ 37 , 44 ]. In their study, Gordon et al analyzed 77,797 patients who underwent elective THA in 2019 (n = 43,667) and 2020 (n = 34,130) and noticed a 24.5% decline of this procedure [ 45 ]. Another study conducted on 17,039 patients admitted for joint replacement surgery in university and community hospitals in Taiwan revealed an even greater reduction, of about 60%, of these procedures during the COVID-19 pandemic [ 46 ].…”
Section: Discussionmentioning
confidence: 99%